Pengaruh Motivasi, Kepuasan Kerja Dan Komunikasi Kerja Terhadap Kinerja Karyawan CV. Jaya Harapan - Imam Buchori; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to study Motivation, Satisfaction and communication, on the Performance of Student Activities Unit of the Faculty of Economics and Business. While the variables used in this study are Performance variables as the dependent variable, while the independent variables are Motivation, Satisfaction and communication styles. Data were collected through a questionnaire method with a total sample of 69 respondents.The results of this study together conclude that there is an influence between motivation, satisfaction and communication, and on performance and partially conclude that there is an influence between motivation, satisfaction and communication, and on performance. Keywords: Motivation, Satisfaction and communication, performance